Geographic Information System for Mapping the Area and Coconut Production in Kendal Regency - Aan Kia Asshifa; Bambang Agus Herlambang; Ahmad Khoirul Anam (Yayasan Kita Menulis, 2025)
Coconut fruit holds high economic value as it can be utilized for various products and significantly contributes to the local economy. This research aims to develop a Geographic Information System (GIS) to map land area and coconut production in Kendal Regency in 2023 as a foundation for more efficient resource management. By integrating spatial and non-spatial data from the Central Statistics Agency (BPS), this GIS visualizes the spatial distribution of coconut plantations and identifies production variations among sub-districts. The analysis reveals that Patebon Sub-district has the highest coconut production, while Cepiring Sub-district, despite having the largest land area, records relatively low production. Mapping was conducted using Quantum GIS (QGIS) software, allowing for accurate and efficient data digitization. This GIS output holds significant potential to support spatial planning, data-driven policy formulation, and the improvement of coconut farmers' welfare in Kendal Regency. The implementation of the map on a web-based platform facilitates public access to the presented spatial information.